"Fifth‐day fits" revisited: A literature review of benign idiopathic neonatal seizures and comparison with KCNQ2‐ and KCNQ3‐associated benign familial epilepsy syndromes - Varun Kannan; Aishwarya V. Pareek; Abhijit R. Das; Charles T. Gay; James J. Riviello Jr (Wiley, 2023)
Abstract Benign idiopathic neonatal seizures (BINS), colloquially referred to as the "fifth‐day fits," is a clinical neonatal epilepsy syndrome associated with early, spontaneous resolution of seizures and favorable developmental outcome. Although this disease entity was first described over four decades ago, the etiopathogenesis remains unknown, and it is unclear if the syndrome represents a single, cohesive disorder or a common manifestation of various unrelated neonatal neurological disturbances. As such, there are no standardized approaches to diagnostic workup and management. Benign familial neonatal seizures (BFNS) is a well‐characterized genetic syndrome associated with KCNQ2 and KCNQ3 pathogenic variants, which also manifests clinically with self‐resolving seizures in the neonatal period. While it remains unclear if there is any shared pathogenesis between these two disorders, the exceedingly similar phenotypic presentations and natural history raise the question of whether consensus management approaches used in genetic BFNS can also be applied to BINS. Here, we present a topical and historical review of BINS and BFNS literature and propose specific treatment recommendations based on extrapolation of limited existing clinical data.